2013 International Conference on Quality, Reliability, Risk, Maintenance, and Safety Engineering (QR2MSE) 2013
DOI: 10.1109/qr2mse.2013.6625899
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of fault semantic network using Bayesian theory for probabilistic fault diagnosis in process industry

Abstract: Investigating complex interaction patterns among multiple process variables (PVs) is an important task for fault propagation analysis and calculation of final risks. This paper demonstrates a robust method to estimate interaction strengths among process variables. The method is based on dynamic fault semantic networks (FSN) combined with Bayesian belief theory for probabilistic tuning of the fault semantic network. The effectiveness and feasibility of the proposed technique is verified on simulated data emanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…As a further development, a method based on dynamic fault semantic networks was presented by Gabbar and Hossein in 2013. 33 The fault semantic network was probabilistically tuned by combining with Bayesian bielief theory. This can be introduced as a robust method that can estimate interaction strengths among process variables.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…As a further development, a method based on dynamic fault semantic networks was presented by Gabbar and Hossein in 2013. 33 The fault semantic network was probabilistically tuned by combining with Bayesian bielief theory. This can be introduced as a robust method that can estimate interaction strengths among process variables.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…As a further development, a method based on dynamic fault semantic networks was presented by Gabbar and Hossein in 2013 . The fault semantic network was probabilistically tuned by combining with Bayesian bielief theory.…”
Section: Introduction and Review Of The Relevant Literaturementioning
confidence: 99%
“…Most of the studies reported in literature on fault diagnosis using neural networks or support vector machine involve chemical systems with a separator as one of its components (Hussain et al, 2013;Rusinov et al, 2013;Salahshoor et al, 2010). This process is selected because it reveals the most common features appearing in industrial processes.…”
Section: Case Studymentioning
confidence: 99%
“…Such predictive and condition monitoring system is being developed at the Energy Safety and Control Laboratory (ESCL) -University of Ontario Institute of Technology (UOIT). It is based on Fault Semantic Network (FSN) methodology (Gabbar, 2007(Gabbar, , 2010Gabbar and Khan, 2010) but in addition to fault detection, diagnosis and prognosis (Hosseini, 2013;Hosseini andGabbar, 2011a, 2011b;Hussain et al, 2013) this system incorporates in itself root-cause and consequence analysis, maintenance work and design change recommendations. The essence of this approach is demonstrated below.…”
Section: Integrated Fsn Networkmentioning
confidence: 99%